Floristika na raziskovalnih taborih študentov biologije - Jogan, Jernej (Natura Sloveniae, 2001)
The article is a review of floristic results of the first 10 Student Biology Research Camps organized in the territory of Slovenia (1988-1998). The author's view on the botanical and pedagogic objectives of floristic activities carried out within the Research Camps is presented. Methodological development of floristic work is also briefly sketched, while the most important results are presented in a table with the most outstanding records as well as with numerical scores of the mapping of vascular plants. Plans for the floristic work in the future are based on the critical evaluation and discussion of the results presented herewith.
Keywords: Botanika; Botany; Classification; Ecosystem; Education; Ekosistem; Plants; Rastline; Rhododendron-Park Bremen